Effect of Different Mating Systems on Magnitude of Inbreeding Depression in Maize - and K.SUPRIYA, P. BINDU PRIYA, T. PRADEEP, K. SUMALINI , D. VISHNU VARDHAN REDDY (The Journal of Research, PJTSAU, 2020)
This experiment was conducted for four seasons i.e., kharif 2016, rabi 2016-17, kharif 2017 and rabi 2017-18 at RegionalAgricultural Research Station, Palem to assess the magnitude of inbreeding depression in different types of crosses (single, threewayand double) in maize following three methods of mating systems viz., self pollination, sib mating and open pollination. Sixcrosses (two each of single, double and three way crosses) were selected wherein three mating systems were imposed i.e.,selfing, sib mating and open pollination. The breeding material was evaluated for 13 traits and advanced from F1 to F4 generation.The results indicated that high degree of inbreeding was observed in selfing followed by sib mating and open pollination. Amongall the generations, F1 to F2 showed high magnitude of inbreeding depression followed by F2 to F3 and F3 to F4. Irrespective of themating system, it was observed that the magnitude of inbreeding depression was high for characters grain yield, fodder yield, earlength, number of kernels per row and 100-kernel weight while lowest inbreeding depression was observed for days to 50 per centtasseling, days to 50 per cent silking and days to maturity. Among the two single crosses, Single Cross-1 (SC-1) recorded highinbreeding depression compared to Single Cross-2 (SC-2). Similarly Three-way Cross-2 (TWC-2) recorded more inbreedingdepression than Three-way Cross-1 (TWC-1) while Double Cross-1 (DC-1) exhibited more inbreeding depression than DoubleCross-2 (DC-2). Single crosses showed higher inbreeding depression over three way and double crosses. As self pollination isa severe form of inbreeding, it reduced the phenotypic values of the genotypes.